Defining optimal enzyme and matrix combination for replating of human induced pluripotent stem cell-derived cardiomyocytes at different levels of maturity - Koç, Arzuhan; Şahoğlu Göktaş, Sevilay; Akgül Çağlar, Tuba; Çağavi, Esra (Elsevier Inc., 2021)
Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) create an unlimited cell source for basic and translational research. Depending on the maturity of cardiac cultures and the intended applications, obtaining hiPSC-CMs as a single-cell, monolayer or three-dimensional clusters can be challenging. Here, we defined strategies to replate hiPSC-CMs on early days (D15-30) or later more mature (D60-150) differentiation cultures. After generation of hiPSCs and derivation of cardiomyocytes, four dissociation reagents Collagenase A/B, Collagenase II, TrypLE, EDTA and five different extracellular matrix materials Laminin, iMatrix-511, Fibronectin, Matrigel, and Geltrex were comparatively evaluated by imaging, cell viability, and contraction analysis. For early cardiac differentiation cultures mimicking mostly the embryonic stage, the highest adhesion, cell viability, and beating frequencies were achieved by treatment with the TrypLE enzyme. Video-based contraction analysis demonstrated higher beating rates after replating compared to before treatment. For later differentiation days of more mature cardiac cultures, dissociation with EDTA and replating cells on Geltrex or Laminin-derivatives yielded better recovery. Cardiac clusters at various sizes were detected in several groups treated with collagenases. Collectively, our findings revealed the selection criteria of the dissociation approach and coating matrix for replating iPSC-CMs based on the maturity and the requirements of further downstream applications.
Keywords: Human Induced Pluripotent Stem Cells; Cardiomyocytes; Cardiac Differentiation; Replating; Cell Dissociation; Dissociation Enzymes; Extracellular Matrix